Covid-19: factors affecting on awareness level of the force majeure clause in the construction contract / Norzaihan Mad Zin and Ezlina Mohd Ahnuar - Mad Zin, Norzaihan; Mohd Ahnuar, Ezlina (UiTM Press, 2022)
The spread of the Covid-19 had forced the whole world to enforce the lockdown where all the business sectors and daily activities were on hold and new norms adopted since 2020 until now. The construction industry was one of the sectors severely affected by this outbreak, including Malaysia. Various construction-related issues arose, and the construction clause on Force Majeure became the talk of the town. Endless discussions and arguments arose regarding determining the Covid-19 impact to the contracting party who plan to seek relief using this clause. Thus, this study aims to evaluate the current awareness and importance of the Force Majeure clause in the construction contract in the realm of the Covid-19 outbreak. This pandemic was a new phenomenon, and there were limited law references that can be referred to in determining the best way to deal with its contractual effects. This study was carried out using a mixed methodology. Semi-structured interviews were conducted with 12 respondents, mainly the contract administration. Questionnaire surveys were distributed to 47 respondents. Interviewed data were analyzed using Atlas-ti 9 software to produce more scientific and well-grounded results, and descriptive analyses were conducted for the questionnaire survey. Finding from this paper reveals that there was a varying level of awareness of the Force Majeure clause, mainly due to a lack of experience in dealing with Force Majeure. There was a significantly different understanding of the actual Force Majeure definition and how the clause can be evoked. The respondents were also unsure how the clause could provide complete protection to the contracting parties. This study also concluded some recommendations to improve the enforcement of the Force Majeure clause for future declaration.